Effects of neonatal nutrition interventions on neonatal mortality and child health and development outcomes: A systematic review. Issue 1 (5th March 2021) - Imdad, Aamer; Rehman, Faseeha; Davis, Evans; Ranjit, Deepika; Surin, Gamael S. S.; Attia, Suzanna L.; Lawler, Sarah; Smith, Abigail A.; Bhutta, Zulfiqar A.
Abstract: Background: The last two decades have seen a significant decrease in mortality for children <5 years of age in low and middle‐income countries (LMICs); however, neonatal (age, 0–28 days) mortality has not decreased at the same rate. We assessed three neonatal nutritional interventions that have the potential of reducing morbidity and mortality during infancy in LMICs. Objectives: To determine the efficacy and effectiveness of synthetic vitamin A, dextrose oral gel, and probiotic supplementation during the neonatal period. Search Methods: We conducted electronic searches for relevant studies on the following databases: PubMed, CINAHL, LILACS, SCOPUS, and CENTRAL, Cochrane Central Register for Controlled Trials, up to November 27, 2019. Selection Criteria: We aimed to include randomized and quasi‐experimental studies. The target population was neonates in LMICs. The interventions included synthetic vitamin A supplementation, oral dextrose gel supplementation, and probiotic supplementation during the neonatal period. We included studies from the community and hospital settings irrespective of the gestational age or birth weight of the neonate. Data Collection and Analysis: Two authors screened the titles and extracted the data from selected studies. The risk of bias (ROB) in the included studies was assessed according to the Cochrane Handbook of Systematic Reviews. The primary outcome was all‐cause mortality. The secondary outcomes were neonatal sepsis, necrotizing enterocolitis (NEC), prevention and treatment of neonatal hypoglycaemia, adverse events, and neurodevelopmental outcomes. Data were meta‐analyzed by random effect models to obtain relative risk (RR) and 95% confidence interval (CI) for dichotomous outcomes and mean difference with 95% CI for continuous outcomes. The overall rating of evidence was determined by the Grading of Recommendations Assessment, Development, and Evaluation (GRADE) approach. Main Results: Sixteen randomized studies (total participants 169, 366) assessed the effect of vitamin A supplementation during the neonatal period. All studies were conducted in low‐ and middle‐income (LMIC) countries. Thirteen studies were conducted in the community setting and three studies were conducted in the hospital setting, specifically in neonatal intensive care units. Studies were conducted in 10 different countries including India (four studies), Guinea‐Bissau (three studies), Bangladesh (two studies), and one study each in China, Ghana, Indonesia, Nepal, Pakistan, Tanzania, and Zimbabwe. The overall ROB was low in most of the included studies for neonatal vitamin A supplementation. The pooled results from the community based randomized studies showed that there was no significant difference in all‐cause mortality in the vitamin A (intervention) group compared to controls at 1 month (RR, 0.99; 95% CI, 0.90–1.08; six studies with 126, 548 participants, statistical heterogeneity I 2 0%, funnel plot symmetrical, grade rating high), 6 months (RR, 0.98; 95% CI, 0.89–1.07; 12 studies with 154, 940 participants, statistical heterogeneity I 2 43%, funnel plot symmetrical, GRADE quality high) and 12 months of age (RR, 1.04; 95% CI, 0.94–1.14; eight studies with 118, 376 participants, statistical heterogeneity I 2 46%, funnel plot symmetrical, GRADE quality high). Neonatal vitamin A supplementation increased the incidence of bulging fontanelle by 53% compared to control (RR, 1.53; 95% CI, 1.12–2.09; six studies with 100, 256 participants, statistical heterogeneity I 2 65%, funnel plot symmetrical, GRADE quality high). We did not identify any experimental study that addressed the use of dextrose gel for the prevention and/or treatment of neonatal hypoglycaemia in LMIC. Thirty‐three studies assessed the effect of probiotic supplementation during the neonatal period (total participants 11, 595; probiotics: 5854 and controls: 5741). All of the included studies were conducted in LMIC and were randomized. Most of the studies were done in the hospital setting and included participants who were preterm (born < 37 weeks gestation) and/or low birth weight (<2500 g birth weight). Studies were conducted in 13 different countries with 10 studies conducted in India, six studies in Turkey, three studies each in China and Iran, two each in Mexico and South Africa, and one each in Bangladesh, Brazil, Colombia, Indonesia, Nepal, Pakistan, and Thailand. Three studies were at high ROB due to lack of appropriate randomization sequence or allocation concealment. Combined data from 25 studies showed that probiotic supplementation reduced all‐cause mortality by 20% compared to controls (RR, 0.80; 95% CI, 0.66–0.96; total number of participants 10, 998, number needed to treat 100, statistical heterogeneity I 2 0%, funnel plot symmetrical, GRADE quality high). Twenty‐nine studies reported the effect of probiotics on the incidence of NEC, and the combined results showed a relative reduction of 54% in the intervention group compared to controls (RR, 0.46; 95% CI, 0.35–0.59; total number of participants 5574, number needed to treat 17, statistical heterogeneity I 2 24%, funnel plot symmetrical, GRADE quality high). Twenty‐one studies assessed the effect of probiotic supplementation during the neonatal period on neonatal sepsis, and the combined results showed a relative reduction of 22% in the intervention group compared to controls (RR, 0.78; 95% CI, 0.70–0.86; total number of participants 9105, number needed to treat 14, statistical heterogeneity I 2 23%, funnel plot symmetrical, GRADE quality high). Authors' Conclusions: Vitamin A supplementation during the neonatal period does not reduce all‐cause neonatal or infant mortality in LMICs in the community setting. However, neonatal vitamin A supplementation increases the risk of Bulging Fontanelle. No experimental or quasi‐experimental studies were available from LMICs to assess the effect of dextrose gel supplementation for the prevention or treatment of neonatal hypoglycaemia. Probiotic supplementation during the neonatal period seems to reduce all‐cause mortality, NEC, and sepsis in babies born with low birth weight and/or preterm in the hospital setting. There was clinical heterogeneity in the use of probiotics, and we could not recommend any single strain of probiotics for wider use based on these results. There was a lack of studies on probiotic supplementation in the community setting. More research is needed to assess the effect of probiotics administered to neonates in‐home/community setting in LMICs.